Perbandingan Metode Dakwah Muhammadiyah dan Dakwah Jama'ah Tabligh Terhadap Perkembangan Pendidikan Islam Masyarakat Bratan Pajang Laweyan Surakarta Tahun 2014-2015 - Nasution, Baruno, Dr. Syamsul Hidayat, M.Ag (2017)
Live in this world should have a basis in order to keep on a straight path and not deviate. Islam has been declared by Allah as the only religion that can be accepted by Allah. This shows that muslims have been on the straight path. What remains is the attitudes of the adherents to maintain perfect religion until the time of death. In Islam it is often heard the word "da'wah" which is closely related to how to deliver core teachings of Islam itself. But in fact, Muslims themselves are not entirely on the same understanding on da'wah. So these things have an impact on the appearance of branches of da'wah for a different interpretation of the view and the method. The difference of views regarding the da'wah is happening in various parts of the world, including in Kampong Bratan, Pajang, Laweyan, Surakarta. In this place, there are various streams of da'wah that mingle in the life of society in teaching Islam. So the problem in this research is "How a comparation of Muhammadiyah Da'wah method and Jama'ah Tabligh Da'wah method is, and what its influence to the development of Islamic education is in Kampong Bratan, Pajang, Laweyan, Surakarta". This research aims to know and compare Muhammadiyah Da'wah method and Jama'ah Tabligh Da'wah method, and its influence to the development of Islamic education in Kampong Bratan, Pajang, Laweyan, Surakarta. The benefits of this research are expected to add insight into the proper method of preaching in a heterogeneous society and provide input towards da'wah activists to see the condition of the as target community of da'wah. This research is qualitative research that generates descriptive data and is a research field due to take in the region of RW VI and IX Kampong Bratan, Pajang, Laweyan, Surakarta. Data collection is carried out by means of observation, interview and documentation, and data analysis is carried out by description qualitative method in inductive approach. The results of this research conclude: (1) The appropriate propagation Method with the character of Bratan society is a method which is smooth and can adjust to the level of intellectual performing, (2) Methods of Jama'ah Tablighs da'wah are less appropriately applied in Kampong Bratan, and (3) Bratan society now are moved for worship due to the appropriate da'wah approach. Keywords: Da'wah, Muhammadiyah, Jama'ah Tabligh, Islamic Education